Clinical efficacy and regulatory mechanisms of Shi Pi Zeng Ye formula in treating functional constipation comorbid with depression: integrating clinical observation, mass spectrometry, bioinformatics, and molecular docking - Yao, Ling; Jia, Xiaoqiang; Li, Yufei; Li, Haixia; Zhang, Zhuhui; Quan, Longfang; Liu, Qiuling; Dai, Jie; Lei, Xuedi; Li, Huashang; Li, Yonghai (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceThe Shi Pi Zeng Ye Formula (SPZY), a traditional Chinese herbal compound, is empirically used for qi and yin replenishment and has been prescribed for managing functional constipation (FC) comorbid with depression. Although its clinical efficacy is recognized, the active constituents and their precise mechanisms of action in treating FC comorbid with depression have yet to be fully determined.Aim of the studyThis research aims to elucidate the efficacy and mechanisms underlying the therapeutic effects of SPZY on FC comorbid with depression, employing a single-arm study design alongside mass spectrometry, network pharmacology, and molecular docking.Materials and methodsIn this study, 202 patients suffering from FC were recruited and treated with SPZY over a 12-week period. The primary outcome measures included the Wexner Constipation Assessment Scale (WCS) and the Hamilton Depression Rating Scale-17 (HAMD-17). Secondary outcomes were evaluated using the Patient Assessment of Constipation Quality of Life (PAC-QOL) and the Hamilton Anxiety Rating Scale (HAMA). Assessments were conducted at baseline, 4 weeks, and 12 weeks post-treatment. The study also explored the action mechanisms of SPZY through mass spectrometry, network pharmacology, and molecular docking to ascertain the binding affinities of SPZY’s active components to critical targets.ResultsThe study findings indicated significant improvements in WCS (p < 0.0001), HAMD-17 (p < 0.0001), PAC-QOL (p < 0.0001), and HAMA (p < 0.001) scores from baseline to 3 months. Mass spectrometry identified Nobiletin, Tangeritin, and Magnolol as pivotal active components of SPZY. Pathological processes potentially modulated by SPZY in FC comorbid with depression include regulation of membrane potential, response to alcohol, regulation of developmental growth, and neuroactive ligand-receptor interaction pathways. Network pharmacology analysis pinpointed SLC6A3 and OPRM1 as central therapeutic targets of SPZY. Molecular docking results suggested that Sugiol, Shinpterocarpin, Medicarpin, and Formononetin have high binding affinities to SLC6A3 and OPRM1, with the SLC6A3-Medicarpin complex exhibiting the strongest binding energy (−9.6 kcal/mol).ConclusionThe SPZY formula is effective in alleviating symptoms of FC and depression. The interaction between SLC6A3 and Medicarpin is identified as a crucial mechanism in the therapeutic efficacy of SPZY for treating FC comorbid with depression.